2021
DOI: 10.23960/jipt.v9i1.p72-84
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Of Production Factor Allocation Of Cattle Breeding Business (Case Study in Asto Mulyo Village, Punggur District, Central Lampung Regency)

Abstract: The purpose of this study was to analyze some factors of beef cattle production in Asto Mulyo Village, Sub-district of Punggur, Central Lampung regency which has the positive effect on production, then carried out an analysis of the allocative efficiency of production factors, to determine the level of efficiency in terms of price factors used in the beef cattle business in Asto Mulyo Village. To test the significance of the factors of production, it is carried out using a regression test with the Cobb-Douglas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…Balai Panjang does not have the NRR value for Indonesian Simmental bulls. This is in accordance with the opinion of [14] stated that the NRR value of male beef cattle in Sriwaderi village was 0%, this was due to beef cattle breeders only being mated with the Artificial Insemination (AI) system, so that the bulls were not raised by breeders as male elders and were sold directly by breeders. Breeders in Nagari Balai Panjang on average are traditional breeders, the high cost of caring for males is one of the reasons breeders do not use males in breeding, besides that if using natural mating with superior males from outside the region, breeders must incur large costs for livestock transportation for one mating.…”
Section: Net Replacement Ratesupporting
confidence: 87%
See 2 more Smart Citations
“…Balai Panjang does not have the NRR value for Indonesian Simmental bulls. This is in accordance with the opinion of [14] stated that the NRR value of male beef cattle in Sriwaderi village was 0%, this was due to beef cattle breeders only being mated with the Artificial Insemination (AI) system, so that the bulls were not raised by breeders as male elders and were sold directly by breeders. Breeders in Nagari Balai Panjang on average are traditional breeders, the high cost of caring for males is one of the reasons breeders do not use males in breeding, besides that if using natural mating with superior males from outside the region, breeders must incur large costs for livestock transportation for one mating.…”
Section: Net Replacement Ratesupporting
confidence: 87%
“…The results of the NI value of Indonesian Simmental Cattle in this study were also higher when compared to research by [17] namely 15.45% NI value of beef cattle in Banai District and [12] with NI value of 18.18% Bali cattle in the Yapen Islands, and higher than research by [14] namely 24.45% NI of Indonesian Simmental Cattle in Sriwaderi Village. This happens due to different livestock rearing systems and environmental factors, in Nagari Balai Panjang it is in the highlands so that Indonesian Simmental cattle can develop well in this area, this is related to livestock productivity, one of which is influenced by the environment where this livestock were developed, in addition to that, more Indonesian Simmental cattle entered Nagari Balai Panjang than cattle that left, which affected the number of breeders of productive age in Nagari Balai Panjang which could increase the value of NI, in contrast to the results of research by [12] who stated that in the Yapen Islands, more female livestock were released in the area compared to the incoming livestock and there were still many rejected livestock kept in the area.…”
Section: Natural Increasecontrasting
confidence: 73%
See 1 more Smart Citation
“…This is in line with earlier report [2] that the normal range of S/C is 1.6 to 2.0 and the ideal value is 1. The S/C value in some cows varies with 1.1 and 1.3 in Bali cattle [31], 1.53 in Kruai cattle [32], 2.07 in PO cattle [33], and 1.79 in another study on Bali cattle [1].…”
Section: Service Per Conceptionmentioning
confidence: 79%
“…The highest average of CR is at parity 2 and 3, while the lowest is at parity 6 and the middle CR percentage is at parity 1, 4 and 5. This showed that cows at parity 2 and 3 with ages of 4-5 years have experienced maturity of reproductive organs and hormonal systems [33]. Meanwhile, in heifers 2-3 years old, the level of the hormone estrogen is still low and causes difficulties in detecting the estrus and affecting the reproductive efficiency of the cows [40].…”
Section: Conception Ratementioning
confidence: 99%